Banquetes rituales en la necrópolis púnica de Gadir - Niveau de Villedary y Mariñas, Ana Mª (Gerión. Revista de Historia Antigua, 2006)
The excavations carried out since the end of the Nineteenth century in Cadiz (Spain) have brought to light a great part of the Punic cemetery (6th-3rd centuries BC) of the ancient Phoenician colony of Gadir. Close to the graves it has been found a group of structures and materials that shows the regular practices of these burials feasts. In order to define the type of food consumed during these ritual meals, as well as to determine its possible symbolic meaning, we analyse, on the one hand the pottery remains (transport containers, cooking pottery and tableware) and, on the other hand, the organic remains (specially those belonging to mammals, fishes and molluscs).